METHODS OF TEACHING CONCEPTS OF MODERN NATURAL SCIENCES FOR HUMANITIES MAJORS. (Journal of Educational Sciences, 2019)
The article deals with the features of teaching the course "the Concept of modern natural science" to students of Humanities faculties. The purpose of this course in higher education is to reveal the unity of natural science knowledge to cover the whole world-from elementary particles and atoms to the galaxy and the Universe as a whole, the world of living and inanimate nature. Introduction to the concepts, principles and approaches of modern natural science. Show the relationship and interdependence of natural Sciences and Humanities. To reveal the unity of nature and man, to find out the role and place of natural Sciences in solving global problems of mankind. The purpose of this course is to familiarize students of Humanities with the contribution of scientists – naturalists in the development and formation of modern scientific ideas, the breadth of scientific interests, the attention of most scientists to the problems of culture, ecology, preservation of civilization. The most important goal of the course is to form a unified natural science view of the world, common to specialists in all areas of higher education.Key words: natural science, humanities,  modeling, case study, hypothesis.